Bicycle fatalities: Trends in crashes with and without motor vehicles in The Netherlands. (April 2017) - Schepers, Paul; Stipdonk, Henk; Methorst, Rob; Olivier, Jake
Highlights: Deaths following motor vehicle crashes in the Netherlands decreased in 1996–2014. Contrarily, cyclist deaths in crashes without motor vehicles increased. Part of the rise of deaths in single crashes is due to more cycling by elderly. Similar trends were found in recent research in Australia. Abstract: Boufous and Olivier (2015) recently found an increasing trend of police-reported cyclist deaths in single-vehicle crashes while a decreasing trend was found for fatal bicycle-motor vehicle crashes. This study sets out to conduct the same trend analyses for the Netherlands using causes of death statistics. The results show that for 1996–2014, the number of cyclist deaths in motor vehicle collisions per km cycled (i.e. the risk) has declined by 3.8% per annum (95% CI: −4.6%, −3.0%) while the risk of cyclist deaths in crashes without motor vehicles increased by 7.0% per annum (95% CI: 5.5%, 8.7%). The large majority of cyclist deaths at the beginning of the study period were due to bicycle-motor vehicle crashes. By 2014, however, the share with motor vehicles was only slightly higher than the share without motor vehicles. We also conducted trend analyses controlling for age by stratifying into nine age groups. After controlling for age, the average annual decrease of cyclist deaths in crashes with motor vehicles was 5.4% (95% CI: −6.0% to − 4.7%). The average annual increase of deaths in crashes without motor vehicles was 4.4% (95% CI: 3.1–5.7%). These trends are more favourable than those without controlling for age which can be explained by more cycling among the elderly who have an elevated risk. We conclude that, similar to Australia, cyclist deaths following motor vehicle crashes in the Netherlands have decreased while deaths without motor vehicles have increased.